Pengaruh Penerapan Metode Turki Utsmani dalam Pembelajaran Tahfiz Al-Qur’an Terhadap Jaudah Hafalan Santri di Pondok Pesantren Al-Qur’an Sirojul ‘Ulum Sungai Lilin Musi Banyuasin - Faisal Fuadi; Duski Ibrahim; Dian Erlina (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research was based on the process of learning peaces tahfidz which was only used the method of conventional or ‘arad al-Qira’ah. That was the students only demonstrated their memorization in front of supervissor without replay their memorization before in terms of methodology. This research was the quantitative research with post-test only control design. The data collection had gotten from observation, documentation and the memorization of al-Qur’an exam. The population in this research was all the male students class of wusth that consisted from four calsses, and the sample were two classes, that was class A and class B. The total students were 44. class A as the experiment class and class Bas the control class. From the data analysis it was concluded that Jaudah or the Quality of memorization al-Qur’an students in Islamic Boarding School al-Qur’an Sirojul ‘Ulum sungai Lilin Musi Banyuasin had categorized as average. It had seen based on the calculation of value “t” at pairred differences which had the value negative (-3,95. it showed that it had the different result, that was thr different average it was happened between Experiment class and Control class had the characteristic of ooposite(away from each other). It was mean the value average of Experiment class was more bigger and underwent significant changed after the students got the treatmentand bassd on the result exam “t “ had gotten ‘t ‘(calculate) as big as -3,95 (it was absolute became 3,95) with df-21 had gotten “t” (table) as big as 1,720 so ‘t’ (calculate) 3,95> t (table) 1,720. In other word, Ha the resaerch that counded. The influence of Applying thr Turkish Utsmani method in the learning tahfiz toward Jaudah or Quality the Syudents memorization had accepted while Ho had rejected.